"Rules of engagement": How experiential learning facilitates the formation of a public-private partnership in Russia. Issue 6 (3rd June 2014) - Mouraviev, Nikolai; Kakabadse, Nada
Abstract : Purpose: – The purpose of this paper is to investigate to what extent one can apply experiential learning theory (ELT) to the public-private partnership (PPP) setting in Russia and to draw insights regarding the learning cycle's nature. Additionally, the paper assesses whether the PPP case confirms Kolb's ELT. Design/methodology/approach: – The case study draws upon primary data which the authors collected by interviewing informants including a PPP operator's managers, lawyers from Russian law firms and an expert from the National PPP Centre. The authors accomplished data source triangulation in order to ensure a high degree of research validity. Findings: – Experiential learning has resulted in a successful and a relatively fast PPP project launch without the concessionary framework. The lessons learned include the need for effective stakeholder engagement; avoiding being stuck in bureaucracy such as collaboration with Federal Ministries and anti-trust agency; avoiding application for government funding as the approval process is tangled and lengthy; attracting strategic private investors; shaping positive public perception of a PPP project; and making continuous efforts in order to effectively mitigate the public acceptance risk. Originality/value: – The paper contributes to ELT by incorporating the impact of social environment in the learning model. Additionally, the paper tests the applicability of ELT to learning in the complex organisational setting, i.e., a PPP.